The path-dependent design of international organizations: Federalism in the World Health Organization - Tine Hanrieder (European Journal of International Relations, 2015)
The article puts forward a historical institutionalist account of how international organizations are `designed.' I argue that deliberate institutional design is circumscribed by path-dependent power dynamics within international organizations. Power-driven path dependence is used to explain that organizations lock in and reinforce historical privileges of international organization subunits. Early winners in the international organization lock in their privileges with the support of member-state allies, and reap increasing returns from their positions over rounds of reform. They thereby amplify features of international organization design that reformers would otherwise change later on. The argument is illustrated with a historical case study of the World Health Organization's unique federal design, which grants the regional offices near autonomy from headquarter oversight. Vocal criticisms of the World Health Organization's regionalization and repeated centralization attempts notwithstanding, the powers of the regions have increased over time. The case study retraces the path-dependent struggles over the World Health Organization's federal design since its creation in the 1940s. While the literature on international organizations tends to reserve inertia and path dependence for constructivist analysis, this article offers a rationalist account of inertia in international institutions.
urn:nbn:de:bvb:19-epub-58716-2; Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation).
Keywords: 330; governance; historical sociology; institutions; intergovernmental organization; International Relations; regionalization